Parameterized Dynamic Routing of a Fleet of Cybercars*. Issue 3 (2016) - Luo, Renshi; Boom, Ton J.J. van den; Schutter, Bart De
Abstract: Due to the nonlinearity of the dynamics of vehicles and the discrete nature of the route decision variables, the dynamic routing problem for a large number of vehicles is computationally very hard to solve. In this paper, two efficient parameterized control methods are proposed for the dynamic routing of a fleet of cybercars in a road network only open to cybercars. With the proposed parameterized control methods, the updates of the routes of cybercars are parameterized and then optimized over the parameters with respect to the overall performance of the cybercar system for a representative set of scenarios. After tuning the parameters, the proposed parameterized control methods are implemented online with fixed parameters. Moreover, the two proposed parameterized control methods are well-structured and scalable, and therefore can be applied to road networks with arbitrary topologies. The effectiveness of the proposed parameterized control methods is shown in a numerical simulation study.